Thermochemistry of ionic liquid-catalysed reactions. Isomerisation and transalkylation of tert-alkyl-benzenes. Are these systems ideal? - Verevkin, Sergey P.; Emel'Yanenko, Vladimir N.; Hopmann, Elisabeth; Arlt, Wolfgang (Journal of Chemical Thermodynamics, 2010)
The chemical equilibrium of mutual interconversions of tert-alkyl-benzenes was studied in the temperature range (286 to 423)K using chloroaluminate ionic liquids as a catalyst. The knowledge of the activity coefficients is required in order to obtain the thermodynamic equilibrium constants K(a). A well established procedure, COSMO-RS, has been used to assess activity coefficients of the reaction participants in the liquid phase. Enthalpies of five reactions of isomerisation and transalkylation of tert-alkyl-benzenes were obtained from temperature dependences of the corresponding equilibrium constants in the liquid phase. For the sake of comparison, high-level ab initio calculations of the reaction participants have been performed using the Gaussian-03 program package. Absolute electronic energy values of the molecules have been obtained using B3LYP and G3MP2 level. Using these results enthalpies of reaction of isomerisation and transalkylation of tert-alkyl-benzenes in the liquid phase based on the first principles are found to be in good agreement with the data obtained from the thermochemical measurements. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Equilibrium; COSMO-RS; Enthalpy of reaction; Alkylbenzenes; Ab initio calculations